EIF2B2 gene mutation causing early onset vanishing white matter disease: a case report - Ilaria Filareto; Giulia Cinelli; Ilaria Scalabrini; Elisa Caramaschi; Patrizia Bergonzini; Elisabetta Spezia; Alessandra Todeschini; Lorenzo Iughetti (BMC, 2022)
Abstract Background Leukoencephalopathy with vanishing white matter (VWM) is an autosomal recessive neurological disease. The physiopathology of disease is still little understood, but it seems to involve impairment in maturation of astrocytes; as a consequence white matter is more prone to cellular stress. Disease is caused by mutations in five genes encoding subunits of the translation initiation factor eIF2B. We know five different types of VWM syndrome classified based different ages of onset (prenatal, infantile, childhood, juvenile and adult onset). Case presentation We report the case of a 4-month-old boy with early seizure onset, recurrent hypoglycemia and post mortem diagnosis of vanishing white matter disease (VMD). At the admission he presented suspected critical episodes, resolved after intravenous administration of benzodiazepines. The brain MRI showed total absence of myelination that suggested hypomyelination leukoencephalopathy. The whole exome sequencing (WES) revealed a variant of EIF2B2 gene (p. Val308Met) present in homozygosity. In this case report we also describe the clinical evolution of seizures, in fact the epileptic seizures had a polymorphic aspect, from several complex partial seizures secondarily generalized to status epilepticus. Conclusion Infantile and early childhood onset forms are associated with chronic progressive neurological signs, with episodes of rapid neurological worsening, and poor prognosis, with death in few months or years. Clinical presentation of epilepsy is poorly documented and do not include detailed information about the type, time of onset and severity of seizures. No therapeutic strategies for VWM disease have been reported.